Universal operational way of definition of a degree сontamination working fuel atomizers engines - Чоха, Ю.М.; Федорчук, О.П. (Proceedings of National Aviation University (archive), 2005)
The technique of diagnosing of a degree of malfunction working fuel atomizers under operating conditions gas-turbine engine is proved.